TENSION-TYPE HEADACHE: TREATMENT STRATEGIES FOR THE MOST PREVALENT PRIMARY HEADACHE DISORDER - Klaudia Martyna Patrzykąt; Anastazja Orłowa; Kamil Turlej; Aleksandra Oparcik; Anita Pakuła; Julia Pawłowska; Kinga Szyszka; Laura Kurczoba; Marta Cieślak; Anna Baranowska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Tension-type headache (TTH) is the most common primary headache disorder that affects the majority of people during their lifetime. This review summarizes the current state of knowledge on its epidemiology, risk factors, pathophysiology, and treatment, highlighting implications for everyday clinical practice. Methods: A narrative literature review was conducted using PubMed/MEDLINE (January 2016-November 2025). Eligible articles addressed the definition and diagnosis of TTH, epidemiology, risk factors, pain mechanisms, acute and preventive pharmacotherapy, or non-pharmacological interventions; randomized trials, trial protocols, observational studies, systematic reviews, meta-analyses, and narrative reviews were included, while non-peer-reviewed publications, animal-only studies, and reports without a clearly defined TTH subgroup were excluded. Results: Tension-type headache (TTH) is characterized by bilateral, pressing pain of mild to moderate intensity, which is derived from interactions between pericranial myofascial nociception, central sensitization, psychological comorbidity, and lifestyle-related factors. For acute attacks, simple analgesics, such as NSAIDs and paracetamol, are usually effective, whereas triptans, ergots, and opioids are not recommended. In frequent or chronic TTH, a low dose of tricyclic antidepressants remains the first-line prophylaxis. Non-pharmacological methods, including exercise therapy, yoga, acupuncture, TENS, lifestyle modification, and psychotherapy, should be considered as part of an individualized, multimodal treatment strategy. Conclusions: Tension-type headache (TTH) requires personalized care that combines careful use of medications and non-pharmacological treatment. Simple analgesics bring substantial relief in most episodic headaches, while preventive (prophylactic) treatment is needed for ongoing or recurring cases. Education on trigger management and medication overuse is required to ensure patient safety and optimal therapy pathways.